2017
DOI: 10.2147/copd.s131062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a simple prototype respiratory muscle trainer on respiratory muscle strength, quality of life and dyspnea, and oxidative stress in COPD patients: a preliminary study

Abstract: BackgroundThe aim of this study was to evaluate the efficiency of a simple prototype device for training respiratory muscles in lung function, respiratory muscle strength, walking capacity, quality of life (QOL), dyspnea, and oxidative stress in patients with COPD.MethodsThirty COPD patients with moderate severity of the disease were randomized into three groups: control (n=10, 6 males and 4 females), standard training (n=10, 4 males and 6 females), and prototype device (n=10, 5 males and 5 females). Respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 55 publications
(69 reference statements)
1
39
1
Order By: Relevance
“…Although a previous study has confirmed that exercise does regulate inflammation in COPD airways and lung tissues (56), the markers of inflammation were not investigated and therefore it is not able to be concluded. In addition, although some studies have demonstrated that aerobic exercise reversed the airway remodeling in asthmatic mice (57,58), the results of the present study suggested that the benefits of exercise on COPD were more significant in terms of respiratory muscle strength, exercise capacity and exercise-induced dyspnea, which is consistent with the conclusions of other previous studies (59)(60)(61).…”
Section: Discussionsupporting
confidence: 91%
“…Although a previous study has confirmed that exercise does regulate inflammation in COPD airways and lung tissues (56), the markers of inflammation were not investigated and therefore it is not able to be concluded. In addition, although some studies have demonstrated that aerobic exercise reversed the airway remodeling in asthmatic mice (57,58), the results of the present study suggested that the benefits of exercise on COPD were more significant in terms of respiratory muscle strength, exercise capacity and exercise-induced dyspnea, which is consistent with the conclusions of other previous studies (59)(60)(61).…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study showed that there was a significant change in pulmonary function test parameters that may indicate an effect on airflow limitation. This was supported by Leelarungrayub et al 23 who studied the effect of a simple prototype device in moderate to severe COPD patients for 6 weeks. The device consisted of six resistors of different diameters (2–7 mm).…”
Section: Discussionmentioning
confidence: 71%
“…Of these, 25 studies (n ¼ 631 subjects) included subjects with respiratory muscle weakness. [17][18][19][22][23][24][25][26][27][28][31][32][33][34]37,38,40,41,43,[45][46][47][48][49]52 Various loads for IMT were 15% of P Imax , 42,46,48 30% of P Imax , 17,28,31,33,38,40,43,51 load progression of 5-35% of P Imax , 23,24 load progression up to 40-50% of P Imax , 21,39,53 load progression up to 60% of P Imax , 18,20,22,[24][25][26][27][28]30,…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…36 Belman et al 19 and Oh 35 used PFLEX equipment, and the load used for IMT was not clear. Leelarungrayub et al 32 used Portex equipment, and load/resistance was set by the tube diameter (ie, 6 mm, 4 mm, and 2 mm) (can be seen in supplementary materials at http://www. rcjournal.com).…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation